THE EFFECT OF ESFONE AND KHLORMEKVAT CHLORIDE ON THE PHOTOSYNTHETIC APPARATUS FORMATION AND TOMATOES’ AND YIELD’ CAPACITY - Буйна, О. І.; Рогач, В. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
One of the perspective directions of modern phyto physiology is the artificial regulation of growth and development of plants by using synthetic compounds among which sufficiently common group is anti-gibberellin preparations. The deceleration of growth processes in plants by activity oppression of apical meristems has accompanied with formation of a powerful photosynthetic surface, a productive mezo structure, acceleration of functioning races of the photosynthetic apparatus. The retardants using allows to delay the certain organs growth of a plant and owing to it it’s possible the redistribution of assimilates flows to household important tissues and organs. To investigate the influence of chlormequat chloride and esfone on morphogenesis, the formation of leaf apparatus and the activity of photosynthetic processes as important components of tomatoes culture yielding capacity. The field researches were conducted on plantations of tomatoes on a farm «Berzhan» in village Horbanivka Vinnytsia region in 2013-2015. The square of research areas is 33 m2, repetition is quintuple. The Bobcat tomatoes were processed by using a knapsack spray with growth inhibitor of chlormequat chloride (0,25%) and esfone (0,15%) to complete wetting of leaves in the budding phase. The selection of material for studying of leaf mezo structural organization was conducted in a phase of a fruit formation beginning. The leaf mesostructural organization was studied on a fixed material by method of A.T. Mokronosov and R.A. Borzenkova. The morphological indicators were studied every 10 days. The area of leaves was studied by weight method. The yielding capacity was determined by method of counting and weighing. A leaf specific surface density, a leaf index, a chlorophyll index and the net productivity of photosynthesis was studied in the phase of active kapro genesis. The investigation suggests results that the processing of plantations of Bobcat tomatoes with 0,25% solution of chlormequat chloride in the budding phase of has positively influenced on the formation of photosynthetic apparatus of the culture in coenosis and has increased the yielding capacity and using 0,15% solution of esfone was not effective. It is investigated that the amount of leaves on the plants of a research variant, the leaf surface area and the wet mass indicators and leaves dry substance have reduced during the action of growth inhibitors. It is shown that synthetic growth inhibitors have thickened the leaf blade of tomatoes by cells excrescence of the main assimilation tissue – chlorenchima. The three years results of studies suggest about the growth of clean productivity indicator of photosynthesis. The given results analysis suggests that noted reducing of the leaf surface area, the amount and leaves mass during the action of chlormequat chloride has compensated the specific surface density increasing of leaves by better development of mezzo structure elements, substantial increasing the chlorophyll content in leaves and the chlorophyll growth index, the net productivity increasing of photosynthesis which have led to the substantial increasing of donor potential of the plant, the excess formation assimilates and as a result the yielding capacity increasing of culture.It is shown that the processing of tomato plants with chlormequat chloride in the phase of budding is a highly effective means of regulation of formation and functioning of the photosynthetic apparatus and productivity of culture. An important task is to ascertain the effects of other anti-gibberellin preparations on the leaf apparatus of tomatoes and productivity of culture.